2017
DOI: 10.1186/s12885-017-3333-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence among Finnish male cobalt production workers in 1969–2013: a cohort study

Abstract: BackgroundThere is inadequate evidence for the carcinogenicity of cobalt and cobalt compounds in humans. Consequently, the International Agency for Research on Cancer (IARC) has evaluated cobalt metal without tungsten carbide as possibly carcinogenic to humans (Group 2B). The aim of the study was to assess the risk of cancer among workers employed in a Finnish cobalt plant since the beginning of production in 1968.MethodsThe study cohort consisted of all males employed by the Finnish cobalt plant for at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Furthermore, a study on transgenic mice clearly showed higher mutant frequency in lung tissue, as compared to controls (Wan et al 2017). In contrast, a recent cohort study on Finnish male cobalt production workers did not observe any increased cancer risk (Sauni et al 2017). These and other in vivo studies are highly valuable for assessing risks related to cobalt-based particles.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, a study on transgenic mice clearly showed higher mutant frequency in lung tissue, as compared to controls (Wan et al 2017). In contrast, a recent cohort study on Finnish male cobalt production workers did not observe any increased cancer risk (Sauni et al 2017). These and other in vivo studies are highly valuable for assessing risks related to cobalt-based particles.…”
Section: Introductionmentioning
confidence: 92%
“…However, excessive concentration of cobalt may damage human health [ 49 ]. Previous studies investigated the association between exposure levels of the cobalt and cancer incidence and reported controversial findings [ 50 52 ]. While some of these studies [ 50 , 51 ] reported that exposure level of the cobalt might increase the risk of cancer of the upper gastrointestinal tract and lungs, Sauni et al [ 52 ] suggest that occupational-exposure to cobalt may not be associated with an increased overall cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive concentration of cobalt may damage human health [33]. Previous studies investigated the association between exposure to cobalt and cancer incidence and reported controversial ndings [34][35][36]. A study by Turkdogan et.al [34] reported that heavy metals such as cobalt could be related to the high prevalence of upper gastrointestinal cancer rates, and another study [35] reported exposure to cobalt might increase the risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Turkdogan et.al [34] reported that heavy metals such as cobalt could be related to the high prevalence of upper gastrointestinal cancer rates, and another study [35] reported exposure to cobalt might increase the risk of lung cancer. On the other hand, Sauni et al [36] suggested that occupational-exposure to cobalt may not be associated with increased overall cancer risk. Our study revealed that cobalt is signi cantly associated with colon cancer incidence in men.…”
Section: Discussionmentioning
confidence: 99%